2019
DOI: 10.1038/s41598-019-48751-8
|View full text |Cite
|
Sign up to set email alerts
|

Different Grp94 components interact transiently with the myocilin olfactomedin domain in vitro to enhance or retard its amyloid aggregation

Abstract: The inherited form of open angle glaucoma arises due to a toxic gain-of-function intracellular misfolding event involving a mutated myocilin olfactomedin domain (OLF). Mutant myocilin is recognized by the endoplasmic reticulum (ER)-resident heat shock protein 90 paralog, glucose regulated protein 94 (Grp94), but their co-aggregation precludes mutant myocilin clearance by ER-associated degradation. When the Grp94-mutant myocilin interaction is abrogated by inhibitors or siRNA, mutant myocilin is efficiently deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…BiP suppresses oligomerization while Grp94 enhances oligomerization (Figure 5). Our findings with Grp94 and proIGF2 are consistent with reports that Grp94 enhances the self-association of the secreted protein myocilin 53 . We find that Grp94 enhances proIGF2 oligomerization by increasing the assembly rate (k+ in Figure 6) rather than from slowing the transition into irreversible aggregates.…”
Section: Discussionsupporting
confidence: 93%
“…BiP suppresses oligomerization while Grp94 enhances oligomerization (Figure 5). Our findings with Grp94 and proIGF2 are consistent with reports that Grp94 enhances the self-association of the secreted protein myocilin 53 . We find that Grp94 enhances proIGF2 oligomerization by increasing the assembly rate (k+ in Figure 6) rather than from slowing the transition into irreversible aggregates.…”
Section: Discussionsupporting
confidence: 93%
“…Gln368* and likely other mid-OLF termination variants share laboratory characteristics of missense variants: the intracellular deposits (Gobeil et al, 2006) exhibit a dominant negative effect with respect to WT myocilin (Gobeil et al, 2004) and are insoluble in Triton X-100 (Shimizu et al, 2000). Such nonfolding termination variants would likely not reach the stage of protein quality control involving Grp94 (Huard et al, 2019(Huard et al, , 2018Marzec et al, 2012;Stothert et al, 2014;Suntharalingam et al, 2012) and thus be identified by different ER chaperones (Ellgaard et al, 2016), leading to different consequences. Further laboratory investigations of termination variants would be informative.…”
Section: Uncertain Significancementioning
confidence: 99%
“…Only pharmacological inhibition, which should stabilize Grp94 in its closed state, both reverts aggregation kinetics and rescues coaggregation (Figure 5d,e). 18,32 In support of the proposal that selective inhibition of Grp94 is a viable therapeutic approach for myocilin-associated glaucoma are preliminary in vivo studies in which the Grp94 inhibitor 4-Br-BnIm was administered to a mouse model of myocilin glaucoma, resulting in a reduction of IOP. 43 Our lab has used a medium-throughput screen to identify additional scaffolds for molecules that could rescue Grp94 from coaggregation with mutant myocilin and promote its degradation, 18 with a plan to extend to larger compound libraries.…”
Section: Aggregationmentioning
confidence: 97%
“…The electrostatic surface potential indicates both positively charged and acidic patches on both the top and bottom face of the propeller . mOLF is isolated as a monomer by size-exclusion chromatography and only low levels of dimer are captured by chemical cross-linking, suggesting that intrinsic dimerization is transient or weak. In sum, CC confers the molecular tetramer and LZ serves as molecular spacers: the tetrameric CC diverges into two parallel LZ dimers to form the Y, to which two pairs of the C-terminal mOLF are flexibly connected via the disordered linker (Figure ).…”
Section: Structure Of Wt Myocilinmentioning
confidence: 99%
See 1 more Smart Citation